Remote exercise snacking and fall-related functional outcomes in older adults: a systematic review including a meta-analysis - Zhang, Simin; Wang, Mingkuai; Lin, Ruting; Shuai, Zhenyu; Lv, Zeping; Wang, Chu; Zhang, Ran; Yang, Tian; Wang, Yubo; Zhang, Xuemin (Frontiers in Physiology, 2026)
BackgroundFalls are a leading cause of injury and death among older adults, yet many encounter barriers to engaging in conventional exercise programs. Remote exercise snacking (ES) refers to performing multiple (≥2 times) short bursts (≤10 min) of exercise of any type or intensity daily in a non-laboratory setting (including multiple sets of interval training), with complete rest or at least a 30-min recovery period between each exercise session, this represents a flexible alternative; however, its effectiveness remains inconclusive. This study addresses an important evidence gap by systematically evaluates the impact of remote exercise snacking on lower-limb muscle performance, balance ability, as well as its acceptability and feasibility in older adults.MethodsA systematic search was conducted in six databases (CINAHL, PubMed, Scopus, Cochrane Library, Web of Science and FMRS) from inception to May, 2025. Two reviewers independently performed study selection, data extraction, and risk of bias assessment following PRISMA guidelines. Studies meet the following eligibility criteria in accordance with PICOS, participants were insufficiently active older adults; intervention involved short bouts of exercise; comparator/control were no specific intervention; the primary outcomes was lower-limb muscle function, with secondary outcomes included balance and/or participant adherence or acceptbility; and study design were randomized crossover or randomized control only. Muscle performance and balance outcomes were synthesized through meta-analysis using Stata v15.1 with standardized mean difference (SMD), while adherence and acceptability were evaluated narratively.ResultsFour publications comprising ten studies (n = 313, M/F: 170/143) were included. Remote exercise snacking significantly improved lower-limb muscle strength (SMDpooled = 0.29, 95% CI: 0.06–0.52, p = 0.01) and endurance (SMDpooled = 0.24, 95% CI: 0.01–0.46, p = 0.04), but showed no significant effect on balance (SMDpooled = 0.04, 95% CI: −0.14–0.23, p = 0.65). Subgroup analyses showed that greater improvements in strength were observed in interventions lasting 6 weeks or longer and in those that incorporated progression strategies. The overall mean adherence across the included studies was 85%, with adherence generally higher in interventions that provided video-based guidance.ConclusionRemote exercise snacking appears effective in improving lower-limb muscle function but shows limited impact on balance among healthy older adults. Intervention duration and the inclusion of progression are key determinants of efficacy. The delivery mode (e.g., written materials, video, or app-based platforms) and exercise type (e.g., bodyweight, Tai Chi, or combined formats) may influence the acceptability and feasibility of implementation. The main findings are summarized in a graphical abstract.Systematic Review RegistrationIdentifier CRD42024627584.